PscI is a type III secretion needle anchoring protein with in vitro polymerization capacities. Issue 2 (26th February 2015) - Monlezun, Laura; Liebl, David; Fenel, Daphna; Grandjean, Teddy; Berry, Alice; Schoehn, Guy; Dessein, Rodrigue; Faudry, Eric; Attree, Ina
Summary The export of bacterial toxins across the bacterial envelope requires the assembly of complex, membrane‐embedded protein architectures. Pseudomonas aeruginosa employs type III secretion (T3S) injectisome to translocate exotoxins directly into the cytoplasm of a target eukaryotic cell. This multi‐protein channel crosses two bacterial membranes and extends further as a needle through which the proteins travel. We show in this work that PscI, proposed to form the T3S system (T3SS) inner rod, possesses intrinsic properties to polymerize into flexible and regularly twisted fibrils and activates IL‐1β production in mouse bone marrow macrophages in vitro. We also found that point mutations within C‐terminal amphipathic helix of PscI alter needle assembly in vitro and T3SS function in cell infection assays, suggesting that this region is essential for an efficient needle assembly. The overexpression of PscF partially compensates for the absence of the inner rod in PscI‐deficient mutant by forming a secretion‐proficient injectisome. All together, we propose that the polymerized PscI in P. aeruginosa optimizes the injectisome function by anchoring the needle within the envelope‐embedded complex of the T3S secretome and – contrary to its counterpart in Salmonella – is not involved in substrate switching.